AIR QUALITY MONITORING AND STRATEGY IN INDONESIA - P.L. Coutrier; Saut M. Lubis; Noegroho Hadi (Scientific Contributions Oil and Gas, 1994)
BAPEDAL, The Environment Impact Management Agency is responsible for the air pollution control. In addressing the air pollution BAPEDAL launched the "Blue Sky Program". This program consist of two component, air pollution from the mobile sources and the air pollution from stationary sources.